Paternal uncertainty and the economics of mating, marriage, and parental investment in children - Dirk Bethmann; Michael Kvasnicka (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
We develop a theoretical model of mating behavior and parental investment in children under asymmetry in kin recognition between men and women that provides a microfoundation for the institution of marriage. In the model, men and women derive utility from consumption and reproductive success, which is a function of the number and quality of own offspring. Because of paternal uncertainty, men unlike women may err in investing resources in offspring that is not biologically theirs. As a socially sanctioned commitment device among partners, the institution of marriage reduces this risk by restraining promiscuity in society. Both women and men are shown to benefit from lower levels of paternal uncertainty, as does average child quality because of increased parental investments. As an analytical framework, the model is suitable to study a number of societal, economic, and technological changes in their effects on marriage patterns. A combination of factors is argued to underlie the demise of marriage.
Keywords: D10; J12; J13; D02; 330; Mating; Paternal Uncertainty; Parental Investment; Marriage